Question #1e174 Calculus Basic Differentiation Rules Chain Rule 1 Answer Tiago Hands Nov 1, 2016 y=1/(sqrt(2x-1)) y^-1=sqrt(2x-1) y^-2=2x-1 Use implicit differentiation... -2y^-3*(dy)/(dx)=2 -y^-3*(dy)/(dx)=1 -1/y^3*(dy)/(dx)=1 Multiply both sides of the equation by -y^3... (dy)/(dx)=-y^3 (dy)/(dx)=-(1/(sqrt(2x-1)))^3 Answer link Related questions What is the Chain Rule for derivatives? How do you find the derivative of y= 6cos(x^2) ? How do you find the derivative of y=6 cos(x^3+3) ? How do you find the derivative of y=e^(x^2) ? How do you find the derivative of y=ln(sin(x)) ? How do you find the derivative of y=ln(e^x+3) ? How do you find the derivative of y=tan(5x) ? How do you find the derivative of y= (4x-x^2)^10 ? How do you find the derivative of y= (x^2+3x+5)^(1/4) ? How do you find the derivative of y= ((1+x)/(1-x))^3 ? See all questions in Chain Rule Impact of this question 1671 views around the world You can reuse this answer Creative Commons License